Kemalism as a fixed variable in the Republic of Turkey history, society, politics - Berger, Lutz 1969-; Düzyol, Tamer 1982- (Ergon Verlag, 2020)
Since its foundation, Kemalism has played a significant role in the political and social life of the Republic of Turkey. At the same time, Kemalism is one of the most controversial terms in Turkish political life. It is connected to historical personalities like its eponym Mustafa Kemal Atatürk as well as other personalities like İsmet İnönü, Recep Peker and more. This volume illustrates different aspects of Kemalism and highlights the positive and negative incidents and reforms associated with it
Keywords: Kemalismus; Türkei; Aufsatzsammlung